Knowledge, attitudes, and practice behaviors of Norwegian pharmacy workers toward the use of herbal products and dietary supplements by dementia patients - Movahedi, Hamideh (UiT Norges arktiske universitet, 2015)
The aim of the study is to investigate the knowledge, attitudes and practical behaviour of pharmacy workers in Nordland County of Norway concerning the use of HPs and DS by dementia patients. Hundred and five pharmacy workers responded to the electronic questionnaire. 98% of the pharmacy workers have received questions about the HPs and DS. The pharmacy workers used different sources to get knowledge and information about HPs and DS The results of the survey indicate that 17% of pharmacy workers check the possible drug-HPs and DS interactions as a routine. But, 91% percent supply information on drug-HPs and DS interaction and side effects of HPs and DS at least sometimes. The knowledge of pharmacy workers about HPs and DS as a whole needs to be improved. There is a lack of product independent information and also availability of information about HPs and DS in most of the pharmacies in Nordland county of Norway. Pharmacy workers in Nordland County do not routinely document or monitor dementia patients’ use of DS and HPs. Furthermore, most of the pharmacy workers believe that general practitioners have a very important role as safety provider for dementia patients and see themselves less responsible.